Language teaching and skill learning - Johnson, Keith, 1958- (Oxford, UK ; Cambridge, Mass. : Blackwell, 1996)
Language and cognition. Language as skill. Second-language learning and universal grammar. A model for second-language learning and acquisition. Declarative knowledge. The processing dimension...
Keywords: Language and languages; Modern languages; Language and languages -- Study and teaching -- Great Britain; Languages, Modern -- Study and teaching -- Great Britain